POSTMODERN SOCIETY AND COVID-19 PANDEMIC: OLD, NEW AND SCARY - MAMZER, HANNA (Society Register, 2020)
Critical events of a dangerous progression, such as the COVID-19 pandemic, may become the turning points in the functioning of entire societies. Such events obviously foster changes. They disrupt the sense of ontological security, generate fears and enforce change in the organization of social relations, also in a creative and positive manner. In addition to these effects, they also induce many others. They are a magnifier enabling you to see how modern societies are functioning. Therefore, a pandemic allows to see and describe more clearly the characteristics of postmodern human communities. Some of these characteristics (e.g. group functioning) are essentially constant and unchangeable for humans as a species. In turn, some features are very specific, characteristic for a given time, type of events and nature of participating communities. In this text, based on the desk-research methodology and non-systematic participant observation, I indicate the unchanging characteristics of human communities that emerge in the moments of crisis. I also present the specific features of postmodern communities that have been highlighted by the pandemic. I try to indicate the effects of the pandemic on social relations in the future.